Pemberian scaffolding untuk menyelesaikan soal cerita materi perbandingan senilai dan berbalik nilai - Yulina Larasati; Helti Lygia Mampouw (Math Didactic: Jurnal Pendidikan Matematika, 2018)
This qualitative research aims to describe the results of scaffolding in helping students solve the problem of comparative matter of worth and the ratio of reversed values. The main instrument in this study is the researchers themselves, assisted test sheets and interview guides. Subject consisted of 3 students of class VIII SMP N 1 Tengaran with Low-ability math. Subjects, have studying comparative material worth and turning value and making the most mistakes in solving the problem of comparative matter worth of value and turning value. Data of students mistake are grouped by Newman’s error analysis. The results of this grouping became the basis of the scaffolding. The design of scaffolding is 3 levels of Anghileri namely environmental provisions, explaining, reviewing and restructuring and developing conceptual thinking. The results showed that the most mistakes made by the subject is a transformation error. Error reading and error understanding problem solved with reviewing. Transformation errors and skill errors are handled by explaining and restructuring. Error writing answers and mistakes carelessly corrected by reviewing. Proven provision of such scaffolding can help students to correct errors in solving the problem of comparative matter worth of value and turning value.